2020
DOI: 10.21827/jve.3.35748
|View full text |Cite
|
Sign up to set email alerts
|

Virtual exchanges as complex research environments: facing the data management challenge. A case study of Teletandem Brasil

Abstract: Although there is a move toward open data, with research funding bodies more frequently requiring data management plans and dissemination strategies, the data management challenges inherently linked to virtual exchange research are understudied. Data collection is often reported upon in papers addressing interaction analysis or language development, but little attention has been paid to offering critical discussion of data collection and structuration methods or practical advice to encourage data/corpora disse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…MulTeC is a multimodal corpus that includes files generated from Teletandem partnerships established between São Paulo State University (UNESP) in Brazil, São José do Rio Preto campus, and University of Georgia (UGA) in the United States in the years 2012 until 2015. According to Lopes (2019), and Aranha and Wigham (2020), the corpus includes 581 hours of teletandem oral sessions, 666 learning diaries from Brazilian learners, 91 initial questionnaires, 41 final questionnaires, 956 texts written by Brazilian students, and 355 chat registers from 282 participants, who consented to sharing their data for research. Data is organized in tree files, separated according to the modality, year, semester, and groups.…”
Section: Methodsmentioning
confidence: 99%
“…MulTeC is a multimodal corpus that includes files generated from Teletandem partnerships established between São Paulo State University (UNESP) in Brazil, São José do Rio Preto campus, and University of Georgia (UGA) in the United States in the years 2012 until 2015. According to Lopes (2019), and Aranha and Wigham (2020), the corpus includes 581 hours of teletandem oral sessions, 666 learning diaries from Brazilian learners, 91 initial questionnaires, 41 final questionnaires, 956 texts written by Brazilian students, and 355 chat registers from 282 participants, who consented to sharing their data for research. Data is organized in tree files, separated according to the modality, year, semester, and groups.…”
Section: Methodsmentioning
confidence: 99%
“…Within this small body of research, pedagogical and digital skills are observed at specific moments and not longitudinally, as is the case with the studies collected in Guichon & Tellier (2017) based on the ISMAEL corpus. Longitudinal corpora of DVC CMC do exist, such as the one developed within the Teletandem Brasil project (Aranha & Wigham 2020), but these do not focus specifically on teacher training and on the development of online language teaching skills. Moreover, most of these projects and related studies focus on only one telecollaboration model, which precludes a comparative approach that would enable researchers to determine which skills require formal training.…”
Section: Literature Review and Limitationsmentioning
confidence: 99%
“…For an overview of research articles that report empirical studies on teletandem see Rampazzo and Cunha (2021). 6 See Aranha and Lopes (2019b) and Aranha and Wigham (2020), for instance. 7 The authors selected research articles following the criteria: (i) articles were peer-reviews; (ii) data reported on partnerships between Brazil and other countries; (iii) they were empirical studies; (iv) the language of publication was Portuguese, English, or Spanish; (v) they were fully available online.…”
Section: Research In Al and Ttdmentioning
confidence: 99%
“…In this context, the bulk of research in teletandem so far is focused on the qualitative approach and somehow restricted to specific cohorts/partnerships. MulTeC (Multimodal Teletandem Corpus) (LOPES, 2019;LOPES, 2019b;WIGHAM, 2020)…”
Section: Introductionmentioning
confidence: 99%